Limit Cycles of a Class of Perturbed Differential Systems via the First-Order Averaging Method - Amor Menaceur; Salah Mahmoud Boulaaras; Amar Makhlouf; Karthikeyan Rajagobal; Mohamed Abdalla (Complexity)
By means of the averaging method of the first order, we introduce the maximum number of limit cycles which can be bifurcated from the periodic orbits of a Hamiltonian system. Besides, the perturbation has been used for a particular class of the polynomial differential systems.